ANALISIS ANTARMUKA APLIKASI NAVYFRIEND MENGGUNAKAN METODE USABILITY TESTING - Candana, Ronald; Baizul Zaman; Syamsul Bahri (STMIK KHARISMA Makassar, 2024)
The research aims to analyze the usability level of the NavyFriend application in three aspects: effectiveness, efficiency, and user satisfaction. Testing was conducted by providing 5 task scenarios to 20 respondents to measure the effectiveness and efficiency of the NavyFriend application. This was followed by administering the SUS questionnaire to assess the satisfaction aspect experienced by the respondents after using the NavyFriend application. The test results showed an average score of 100% for the effectiveness and efficiency aspects, while the satisfaction aspect obtained an average score of 64. It can be concluded that the user experience is still lacking, as the score of 64 including into the